The Involution of the Storm Corner: Sean Bonney’s Occult - Christina Chalmers (Journal of British and Irish Innovative Poetry, 2022)
This essay constructs an understanding of Sean Bonney’s occult poetics, especially in his prose-poem ‘Second Letter on Harmony’, through its mediation of past traditions of ‘occult poetry’—specifically, Stephen Jonas and the Boston school—with the philosophy of history of Ernst Bloch in Heritage of our Times and Bertolt Brecht’s uses of alienation, particularly the notion of ‘gesture’. Bonney’s methods of apprehending a multifaceted reality, composed of darkness, antipodes, contraries and hiddenness, as much as clarity, self-sameness, light and truth, are related to although different from the occult’s methods of transformation which make the hidden ‘visible’. I argue that Bonney estranges already estranged and fetishised knowledges and facts in their contradictoriness, as a mode of turning knowledge ‘inside out’, whose results are channelled towards anti-fascist struggle and revolutionary praxis. Bonney’s occult poetics seeks to re-appropriate zones of fascist cultural hegemony, such as the occult, making these ripe for revolutionary rediscovery. This very practice sets out a materialist means of communicating with the dead.